Peran Bhabinkamtibmas Dalam Mencegah Terjadinya Tindak Pidana Curanmor Di Wilayah Hukum Polsek Ciamis - Benjamin Yusuf Zakaria (Indonesian Journal of Police Studies, 2020)
ABSTRACT The theft cases in the jurisdiction of the Ciamis Sector Police are quite high. Most theft cases that occur in the jurisdiction of the Ciamis Police Station are motorcycle theft cases. To prevent this from happening, preventive measures have been taken for the community to reduce the high rate of fraud in the jurisdiction of the Ciamis Sector Police. This study discusses the role of Bhabinkamtibmas in preventing the occurrence of motorcycle theft in the Ciamis police area and what factors influence the duty of Bhabinkamtibmas in preventing motorcycle theft, and also to find out what efforts have been made by Bhabinkamtibmas Ciamis Sector Police to prevent motorcycle theft. Conceptual literature contains two research results that are relevant to this study. The theory that the author uses in this study is based on the theory of roles and management theory. The concept used by the author is the concept of Bhabikamtibmas and the concept of motorcycle theft. The approach used in this study is a qualitative approach. The focus of the study is members of Bhabinkamtibmas. The sources used are primary and secondary sources. Data collection techniques are by interview, observation and document study. The author uses triangulation techniques in determining the validity of the data. The findings in the field show that the members of the bhabinkamtbmas were still less than optimal when carrying out their duties, and there was no sincerity to carry out their duties properly. No one has implemented the dikjur binmas, the lack of available members of the Bhabinkamtibmas members, the lack of supporting facilities and the lack of skilled members to make appeals to the public. there are no special methods used, there are also members of the bhabinkamtibmas who still do not master the characteristics of the people in their target villages. As a suggestion, the leader should complete the deficiencies in carrying out the task so that the needs of Bhabinkamtibmas members are met. Members of the Bhabinkamtibmas personnel also need to take part in the education and training program. Efforts in carrying out its efforts to prevent motorcycle theft in the jurisdiction of the Ciamis police sector are still not optimal because there are shortcomings in planning, organizing, acting, controlling. Keywords: The role of Bhabinkamtibmas, preventing occurrence, motorcycle theft